Therapeutic Antibodies - Chernajovsky, Yuti.; Nissim, Ahuva; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
Antibody therapeutics are the treatment of choice for several autoimmune and oncological conditions and are becoming the molecules of choice for further combination therapies and cell engineering. Current developments and clinical successes are summarised by experts in the drug development field. A must read for immunologists, clinical scientists and novel drug developers.
Historical Development of Monoclonal Antibody Therapeutics -- Preclinical Safety Evaluation of Monoclonal Antibodies -- Molecular Developments in Antibody Production -- Engineering Antibodies for Stability and Efficient Folding -- Human Monoclonal Antibodies from Transgenic Mice -- Antibodies to Cytokines -- Anti-TNF Antibodies: Lessons from the Past, Roadmap for the Future -- Therapeutic Anti-VEGF Antibodies -- Humanized Antihuman IL-6 Receptor Antibody, Tocilizumab -- Antibodies to Cell Markers -- Anti-CD20Monoclonal Antibody in Rheumatoid Arthritis and Systemic Lupus Erythematosus -- Herceptin -- The Use of CD3-Specific Antibodies in Autoimmune Diabetes: A Step Toward the Induction of Immune Tolerance in the Clinic -- Monoclonal Antibody Therapy for Prostate Cancer -- Anti-IgE and Other Antibody Targets in Asthma -- Development of Antibody-Based Cellular and Molecular Therapies -- Cytokine, Chemokine, and Co-Stimulatory Fusion Proteins for the Immunotherapy of Solid Tumors -- The T-Body Approach: Redirecting T Cells with Antibody Specificity -- Intracellular Antibodies (Intrabodies) and Their Therapeutic Potential.
Keywords: Medicine; Cancer research; Human genetics; Immunology; Pharmacology; Biomedicine; Pharmacology/Toxicology.; Immunology; Human Genetics; Cancer Research; Electronic books